Outdoor living: a preliminary survey of outdoor, multifunctional domestic spaces in mainland Greece - Jazwa , Kyle A. (Journal of Greek Archaeology, 2024)
This paper focuses on the identification, diversity, and use of multifunctional domestic spaces in ancient and prehistoric Greece. One particularly common yet frequently underexplored type of multifunctional domestic space is the outdoor activity area. The lack of attention given to such spaces is largely owed to the fact that, in most periods and places, domestic structures lacked clear definitions around exterior spaces that overtly signaled their use by one or more households. As a result, it can be difficult for archaeologists to identify such spaces. Making the identification even more difficult, artifacts left behind in exterior spaces are typically more exposed to the elements than objects stored inside and are thus more likely to be poorly preserved and/or out of their original contexts. Archaeologists, therefore, often rely upon indirect evidence, such as specially prepared surfaces and other built infrastructure (e.g., hearths, bothroi [dug/constructed pits]), to identify the use of such spaces and their domestic associations.